A new recombinant rabies virus expressing a green fluorescent protein: A novel and fast approach to quantify virus neutralizing antibodies. (May 2019) - Qin, Shuyun; Volokhov, Dmitriy; Rodionova, Elvira; Wirblich, Christoph; Schnell, Matthias J.; Chizhikov, Vladimir; Dabrazhynetskaya, Alena
Abstract: The Rapid Fluorescent Focus Inhibition Test (RFFIT) is a standard assay used to detect and assess the titers of rabies virus neutralizing antibodies (RVNA) in blood sera. To simplify the multistep RFFIT procedure by eliminating the immunostaining step, we generated a new recombinant RV expressing a green fluorescent protein (rRV-GFP) and assess its suitability for quantifying RVNA. We rescued the rRV-GFP virus from plasmid DNA carrying a full-length genome of the CVS-N2c strain of RV in which the eGFP gene was inserted between the glycoprotein and RNA-polymerase genes. The recombinant virus was genetically stable and grew efficiently in appropriate cells expressing sufficient GFP fluorescence to detect directly 20 h post infection (hpi). We evaluated the feasibility of using rRV-GFP in RFFIT by comparing RVNA titers in 27 serum samples measured by conventional RFFIT and RFFIT-GFP. A linear regression analysis of the data demonstrated a good agreement between these two methods (r = 0.9776) including results with samples having RVNA titers close to the minimally acceptable vaccine potency threshold (0.5 IU/ml). Study results showed that the rRV-GFP virus could replace the CVS-11 challenge virus currently used in the conventional RFFIT and enabling more rapid, simpler, and less expensive detection and quantitation of RVNA.